Dual inhibition of MEK and PI3Kβ/δ–a potential therapeutic strategy in PTEN-wild-type docetaxel-resistant metastatic prostate cancer - Ruiz de Porras, Vicenç; Bernat-Peguera, Adrià; Alcon, Clara; Laguia, Fernando; Fernández-Saorin, Maria; Jiménez, Natalia; Senan-Salinas, Ana; Solé-Blanch, Carme; Feu, Andrea; Marín-Aguilera, Mercedes; Pardo, Juan Carlos; Ochoa-de-Olza, Maria; et al. (Frontiers in Pharmacology, 2024)
Background: Docetaxel remains the standard treatment for metastatic castration-resistant prostate cancer (mCRPC). However, resistance frequently emerges as a result of hyperactivation of the PI3K/AKT and the MEK/ERK pathways. Therefore, the inhibition of these pathways presents a potential therapeutic approach. In this study, we evaluated the efficacy of simultaneous inhibition of the PI3K/AKT and MEK/ERK pathways in docetaxel-resistant mCRPC, both in vitro and in vivo.: Docetaxel-sensitive and docetaxel-resistant mCRPC cells were treated with selumetinib (MEK1/2 inhibitor), AZD8186 (PI3Kβ/δ inhibitor) and capivasertib (pan-AKT inhibitor) alone and in combination. Efficacy and toxicity of selumetinib+AZD8186 were tested in docetaxel-resistant xenograft mice. CRISPR-Cas9 generated a PTEN-knockdown docetaxel-resistant cell model. Changes in phosphorylation of AKT, ERK and downstream targets were analyzed by western blot. Antiapoptotic adaptations after treatments were detected by dynamic BH3 profiling. Results: PI3K/AKT and MEK/ERK pathways were hyperactivated in PTEN-wild-type (wt) docetaxelresistant cells. Selumetinib+AZD8186 decreased cell proliferation and increased apoptosis in PTENwt docetaxel-resistant cells. This observation was further confirmed in vivo, where docetaxel-resistant xenograft mice treated with selumetinib+AZD8186 exhibited reduced tumor growth without additional toxicity.Conclusions: Our findings on the activity of selumetinib+AZD8186 in PTEN-wt cells and in docetaxel-resistant xenograft mice provide an excellent rationale for a novel therapeutic strategy for PTEN-wt mCRPC patients resistant to docetaxel, in whom, unlike PTEN-loss patients, a clinical benefit of treatment with single-agent PI3K and AKT inhibitors has not been demonstrated. A phase I-II trial of this promising combination is warranted.